2022
DOI: 10.18203/issn.2455-4529.intjresdermatol20221637
|View full text |Cite
|
Sign up to set email alerts
|

Injectable platelet rich fibrin therapy for androgenetic alopecia: a series of 15 cases

Abstract: <p>Androgen dependent hair loss is the most common cause of progressive hair loss due to androgenetic miniaturization of hair follicles. Grade 1 and 2 of alopecia is managed well with topical and oral modalities, however grade 3 onwards the need adjuvant treatment arises. To evaluate the efficacy, safety profile and feasibility of injectable-platelet rich fibrin (I-PRF) in androgenetic alopecia and assess the patient satisfaction with this new treatment modality, we conducted a pilot study. Here, 15 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…17 Similarly, in another study, marked visible changes were reported in clinical photographs and dermoscopy after injectable-platelet rich fibrin (analogous to GFC therapy) among Indian patients with androgenetic alopecia by the end of 2 months post-therapy. 18 The hair pull test also showed a pronounced improvement as compared to the baseline result of the same which is comparable to the study performed by Steward and coworkers, in which only one (5%) out of 20 patients had an increase in hair fall in the hair pull test as compared to the results of the hair pull test done preoperatively. 19 Scalp pain during injections was the most common adverse event reported in the present study, which was related to injection pricks, followed by erythema and scalp irritation during healing.…”
Section: Discussionsupporting
confidence: 86%
“…17 Similarly, in another study, marked visible changes were reported in clinical photographs and dermoscopy after injectable-platelet rich fibrin (analogous to GFC therapy) among Indian patients with androgenetic alopecia by the end of 2 months post-therapy. 18 The hair pull test also showed a pronounced improvement as compared to the baseline result of the same which is comparable to the study performed by Steward and coworkers, in which only one (5%) out of 20 patients had an increase in hair fall in the hair pull test as compared to the results of the hair pull test done preoperatively. 19 Scalp pain during injections was the most common adverse event reported in the present study, which was related to injection pricks, followed by erythema and scalp irritation during healing.…”
Section: Discussionsupporting
confidence: 86%
“…Leukocyte counts: higher in low RCF Platelet counts: higher in the low and medium RCF ranges Total GFs release of PDGF-BB, TGF-β1, and EGF: higher in the low and medium RCF ranges VEGF and MMP-9: higher in the low RCF Choukroun J, et al 16 6 2400 (high), 1200 (medium), 600 (low) 8 Leukocyte and Platelet counts: higher in low RCF Total GFs release: higher in low RCF VEGF and TGF-β1: higher in the medium RCF Miron RJ, et al 3-6 min were used in most studies. 7,21,22 Two of the studies used high centrifugation speeds of 1500 and 3000 rpm for 5 and 10 min.…”
Section: Authors Cases Centrifugation Force (Rpm) Time (Min) Resultsmentioning
confidence: 99%
“…This specific type of hair loss is usually addressed using FDA-approved treatments like minoxidil and oral finasteride, which have demonstrated efficacy for addressing grades 1 and 2 of hair loss. 37 However, for individuals experiencing more advanced stages of hair loss (grade 3 and beyond), additional treatment possibilities might be required. Platelet-rich plasma therapy has emerged as a frequently employed approach for promoting hair regrowth in such instances.…”
Section: Understanding Androgenic Hair Loss and Available Treatment O...mentioning
confidence: 99%